Measuring the impact of a bank failure on the real economy: An EU-wide analytical framework - Valerio Paolo Vacca; Fabian Bichlmeier; Paolo Biraschi; Natalie Boschi; Antonio J. Bravo Álvarez; Luciano Di Primio; André Ebner; Silvia Hoeretzeder; Elisa Llorente Ballesteros; Claudia Miani; Giacomo Ricci; Raffaele Santioni; et al. (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
The crisis management framework for banks in the European Union (EU) requires the resolution authorities to identify the existence of a public interest to resolve an ailing bank, rather than to open normal insolvency proceedings (NIPs). The Public Interest Assessment (PIA) determines whether resolution objectives, including the safeguard of financial stability, can be better preserved using resolution tools than NIPs .This paper provides a contribution to the ongoing discussion on the implementation of the PIA, by presenting an analytical framework to quantify the potential impact on the real economy stemming from a bank's failure under NIPs through the interruption of the lending activity ("credit channel"). The framework is harmonized across the jurisdictions belonging to the Banking Union and aims to improve the quantitative leg of the PIA, to be coupled with qualitative elements. In a first step, we quantify the potential credit shortfall faced by firms and households due to the abrupt closure of a bank. In a second step, the impact of the credit shortfall on real outcomes is estimated via a FAVAR model and via a micro-econometric model. Reference values are provided to assess the relevance of the estimated outcomes. The illustrative results show that such a harmonized approach can be applied across the Banking Union and to banks of heterogeneous size. In case of mid-sized banks, this common analytical framework could reduce the uncertainty regarding the extent to which the failure of the institution could have a negative impact to the real economy if the lending activity is interrupted as possibly the case under NIPs.
Keywords: E58; G01; G21; G28; 330; bank resolution; bank insolvency; EU crisis management framework; public interest assessment; bank lending